Dead Space Ventilation Parallels Changes in Scintigraphic Vascular Obstruction at Recurrence of Pulmonary Embolism and after Thrombolytic Therapy: A Case Report - Marc A Rodger; Gwynne Jones; Francois Raymond; Daniel Lalonde; Mike Proulx; Lothar Huebsch; Christopher Bredeson (Canadian Respiratory Journal)
Physiological and alveolar dead space ventilation both increase in pulmonary embolism (PE) in proportion to the severity of vascular obstruction. The case of a patient with recurrent PE while on heparin therapy is presented. The recurrence was characterized clinically by severe pulmonary vascular obstruction and right heart dysfunction. The patient was treated with thrombolytic therapy, with excellent clinical and scintigraphic resolution. Dead space ventilation measurements at baseline, at the time of recurrence and after thrombolytic therapy are presented. The potential utility of dead space ventilation measurements for PE diagnosis and management are discussed.